Simulation study of proton exchange membrane fuel cell cross‐convection self‐humidifying flow channel. (27th October 2020) - Tong, Guangyao; Xu, Xiaoming; Yuan, Qiuqi; Yang, Yi; Tang, Wei; Sun, Xudong
Summary: The proton conducting membrane is the core component of the fuel cell. It needs water to maintain conductivity. Excessive water content inside the fuel cell will block the membrane surface and reduce the output power of the fuel cell. On the other hand, if the water content is too low, the internal resistance of the fuel cell will increase, which will reduce the performance and service life of the fuel cell. Considering the above problems, it is necessary to humidify the air and hydrogen gas before entering the fuel cell, but humidification is to prevent the membrane at the gas inlet from becoming dry. Although proton exchange membrane fuel cell (PEMFC) generates enough water, most of the gas is not completely saturated. This paper designs a self‐humidifying channel to redistribute the distribution of humid gas between different channels, and used FLUENT to simulate the heat and mass transfer, electrical conduction in the fuel cell. The effect of the self‐humidifying flow channel location on the PEMFC water and heat distribution is analyzed and evaluated. Abstract : Humidifying the air and hydrogen before entering the fuel cell is necessary, but humidification is to prevent the membrane at the gas inlet from becoming dry, but most of the gas is not completely saturated. This paper designs a self‐humidifying channel to redistribute the distribution of humid gas between different channels as shown in Figure 2., and used FLUENT to simulate the effect of the self‐humidifying flow channel location on the PEMFC water and heat distribution is analyzed and evaluated.